Association of dynamic changes in arterial partial pressure of carbon dioxide with neurological outcomes in aneurysmal subarachnoid hemorrhage - Rui Su; Hong-Liang Li; Yu-Mei Wang; Linlin Zhang; Jian-Xin Zhou (Heliyon)
Background: Cerebral blood flow (CBF) is closely regulated by carbon dioxide (CO2). In patients with aneurysmal subarachnoid hemorrhage (aSAH), abnormal arterial partial pressure of CO2 (PaCO2) might deteriorate brain injuries. Nevertheless, the impact of dynamic PaCO2 fluctuations on neurological outcomes in aSAH patients has not been extensively studied. Our study aimed to investigate the association between dynamic PaCO2 levels and unfavorable neurological outcomes in aSAH patients. Methods: In this retrospective observational study, we consecutively enrolled 159 aSAH patients from December 2019 to July 2021. Arterial blood gas measurements within 10 days after intensive care unit (ICU) admission for each patient were recorded to calculate the time-weighted average (TWA)-PaCO2, an indicator representing the dynamic changes in PaCO2 levels. For the association between TWA-PaCO2 levels and unfavorable neurological outcomes in aSAH patients, multivariable logistic analysis was used to explore TWA-PaCO2 levels as categorical variables, and restricted cubic spline (RCS) was used to explore TWA-PaCO2 levels as continuous variables. Results: In multivariable logistic analysis, after adjusting confounders, when TWA-PaCO2 35–45 mmHg was as a reference, TWA-PaCO2 < 35 mmHg (odds ratio [OR] 2.15, 95 % confidence interval [CI] 0.83–5.55, P = 0.113) and TWA-PaCO2 > 45 mmHg (OR 8.31, 95 % CI 0.72–96.14, P = 0.090) were not independently associated with unfavorable neurological outcomes (modified Rankin score of 3–6). The RCS shows a “U” shape curve between TWA-PaCO2 levels and unfavorable neurological outcomes, with a nonlinear P-value of 0.023. The lowest ORs of unfavorable neurological outcomes were within PaCO2 32.8–38.1 mmHg. Conclusions: Both lower and higher PaCO2 levels are harmful to aSAH patients. PaCO2 in the range of 32.8–38.1 mmHg is associated with lowest unfavorable neurological outcomes.